Міжнародні наукові зв'язки Федора Вовка: погляд через століття - Франко, О. (Народна творчість та етнографія, 2006)
The article researches the life and scientific activities of the famous Ukrainian ethnologist, anthropologist, archaeologist and a public leader Fedir Vovk (1847 - 1918). A great heritage is left by the scholar, but his most important achievement, as for the author s viewpoint, was the representation of Ukraine and its scientific potential in Europe and the world, as well as forming international scientific connections. F. Vovk’s concepts, that proved physical, linguistic, material and spiritual unity of Ukrainian people, stay topical nowadays.